2015
DOI: 10.1016/j.steroids.2014.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in body composition, cardiometabolic risk factors and insulin sensitivity with trenbolone in normogonadic rats

Abstract: Trenbolone (TREN) is used for anabolic growth-promotion in over 20 million cattle annually and continues to be misused for aesthetic purposes in humans. The current study investigated TREN's effects on body composition and cardiometabolic risk factors; and its tissue-selective effects on the cardiovascular system, liver and prostate. Male rats (n=12) were implanted with osmotic infusion pumps delivering either cyclodextrin vehicle (CTRL) or 2mg/kg/day TREN for 6 weeks. Dual-energy X-ray Absorptiometry assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…In contrast to TEST treatment, TREN additionally reduced VAT mass and restored femoral stiffness and ultimate force/strength (F U ) in these animals. The observed differences between TEST and TREN could be ascribed to TREN's previously reported ability to reduce visceral adiposity [26] more effectively than TEST [35].…”
Section: Androgen Therapy In Visceral Obesity and Testosterone Deficimentioning
confidence: 90%
See 2 more Smart Citations
“…In contrast to TEST treatment, TREN additionally reduced VAT mass and restored femoral stiffness and ultimate force/strength (F U ) in these animals. The observed differences between TEST and TREN could be ascribed to TREN's previously reported ability to reduce visceral adiposity [26] more effectively than TEST [35].…”
Section: Androgen Therapy In Visceral Obesity and Testosterone Deficimentioning
confidence: 90%
“…Pumps were prepared with VEH (45 % w/v 2β-hydroxypropyl cyclodextrin), TREN (suspended in 45 % w/v 2β-hydroxypropyl cyclodextrin) or TEST (suspended in 45 % w/v 2β-hydroxypropyl cyclodextrin). The dosage delivery rate of each steroid was 2.0 mg kg day −1 in accordance with previous work by ourselves using this delivery method demonstrating a therapeutic effect on body composition [26]. All 2β-hydroxypropyl cyclodextrin suspensions were prepared in Milli-Q H 2 0 and passed through a 0.45-μm filter (Millex, Darmstadt, Germany).…”
Section: Infusion Pump Implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, TREN causes a more potent reduction in retroperitoneal/visceral fat pad mass than TEST in hypogonadic male rats (34,35). More recently, we have shown that TREN improves multiple components of the MetS and improves myocardial tolerance to I-R in normogonadic rats (36).…”
mentioning
confidence: 86%
“…Pumps were prepared with vehicle (45% wt/vol 2␤-hydroxypropyl cyclodextrin), TREN (suspended in 45% wt/vol 2␤-hydroxypropyl cyclodextrin), or TEST (suspended in 45% wt/vol 2␤-hydroxypropyl cyclodextrin). The dosage delivery rate of each steroid was 2.0 mg/kg⅐d in accordance with previous work by ourselves using this delivery method and demonstrating a therapeutic effect on body composition (36). All 2␤-hydroxypropyl cyclodextrin suspensions were prepared in Milli-Q H 2 O and passed through a 0.45-m filter (Millex).…”
Section: Infusion Pump Implantationmentioning
confidence: 99%